ANALYTICAL STUDY OF DIGITAL PAYMENT SYSTEM FOR FINANCIAL INCLUSION IN INDIA - Rout, Mamatamayee; Ray, Ratikanta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the current research, the authors consider the emerging opportunities posed by online payment to the improvement of financial inclusion programs in India, in terms, respectively, of transactional behavior, of institutional serviceability, and of modeling coverage. It completely changes the digital banking system, in this particular case, when coming to the villages and semi-urban villages, where it comes down to the systems like UPI, AePS, mobile wallets, etc., mixed methods, i.e., the inclusion of the statistical judgements (ANOVA, regression, correlation) combined with the secondary information provided by the national financial institutions are introduced in an attempt to test the feasibility of the digital payment systems. As the key players quietly seek to discover the results of their inclusions, the key spotlights are volumes of deposits, issue of Rupay cards and provision of credit to MSME. Structural influencing factors at work in issuing loans, the large gender-based relationship with access to the internet, and the large institutional performance discrepancy are all results as well. These are what contributes similarly as to why some of these compromises in the form of an act of parliament and later in the form of knowledgeable infrastructures have to be undertaken to eliminate fatally deprivations. Besides the presented parts of such literature, the 2019 article provides evidence-based discussion regarding how much the scenario of financial inclusion could potentially be influenced by fintech and presents a framework, according to which the issue of research is to be analyzed, besides which policies are issued. It further examines how the behavioral and technical factors would help in bringing the adoption trend. With that stated, the paper goes on to illustrate why digital payment systems are not a tool of inclusive development in the reconfiguration of the Indian financial ecosystem, but rather a proxy.